Research on Big Data Application for Security - Deli Yang; Tao Zhang (Dianxin kexue)
Several data sources of big data on security were described，a closer look was taken at the implementation of big data platform on security，the main points and steps during the implementation were also proposed.Specially，detail analysis on the overall architecture and system structure of the big data platform on security were provided，the relationship with the existing video surveillance platform was also described.The implementation of big data platform on security must be promoted on the scale of data characteristics and algorithm maturity.